Effect of cold Pilger rolling followed by annealing on fatigue crack initiation in Zircaloy-4 alloy cladding tube. (October 2022) - Guo, Wenbin; Li, Geping; Han, Fuzhou; Zhang, Yingdong; Ali, Muhammad; Ren, Jie; Wang, Qichen; Yuan, Fusen
Highlights: Effect of manufacture technology on fatigue crack initiation behavior isinvestigated. The influences of grain size as well as texture on low cycle fatigue properties are considered here based on the Hall-Petch relationship and Schmid factor theory, respectively. The relationship between fatigue crack initiation and microstrain (together with dislocation density) is presented. Abstract: In this study, low cycle fatigue behavior of Zircaloy-4 alloy cladding tube manufactured by cold Pilger rolling and annealing was investigated at room temperature. Results revealed that fatigue cracks initiated toward the marked side on clamped position i.e. on outer wall of the tube. Besides, substantial microstrain and dislocation developed on the out wall surface of the tube during manufacturing stage, which playing a key role in the fatigue crack initiation of the specimens. Meanwhile, effects of grain size and texture of the out wall surface, inner wall surface and cross section remained almost indifferent in this regard.